Malignant acanthosis nigricans: an early diagnostic clue for gastric adenocarcinoma - Yu, Qian (World J Surg Oncol, 2017)
BACKGROUND: Malignant acanthosis nigricans (MAN), characterized by the presence of a hyperpigmented, velvety cutaneous thickening, is recognized as a cutaneous sign of internal malignancy. Few MAN has been reported in the Asian race ever before. CASE PRESENTATION: Here, we report a rare case of MAN with severe mucosa and soles and extraordinary facial involvement in the Asian race. A 74-year-old man presented with hyperkeratotic eruption for 7 months. Physical examination revealed hyperkeratotic plaques on the face, dorsal skin of fingers and heels, and papillomatosis of buccal mucosa. Biopsy findings from skin lesion revealed hyperkeratosis, papillomatosis, and hyperpigmentation of the basal layer. The endoscopic ultrasound with biopsy of the gastric tissue revealed gastric cardia tubular adenocarcinoma. The patient was diagnosed with MAN associated with gastric adenocarcinoma, immediately following tumor resection and lymphadenectomy. A slight improvement was seen in the skin condition but died of cancer cachexia 3 months later. CONCLUSIONS: We report our typical patient to highlight the importance of MAN, which was an early clue to the discovery of gastric adenocarcinoma.